Os processos de subjetivação e o cuidado de si de alunos/karatecas: a instituição escolar e o dojô como formadores de sujeitos - Potulski, Alexsandra Aline (2020)
Through this work, we analyzed the care of the self practices developed by subjects that started the practice of Karate martial art in the workshops performed in full-time schools of Francisco Beltrão and who keeped to practice the art in the dojo space (gym). For this, we accompany the Karate class practices developed at the municipal school Recanto Feliz, an institution located in the city of Francisco Beltrão - PR. The choice of the institution was made due to the fact that it was one of the first to adopt a full-time regime; in addition, this school has been keeping Karate martial art in his activities for approximately 22 years. We also accompany these karatekas on the dojo space, a dedicated place for practicing Karate martial art, located in the same municipality. Both institutions have karate activities carried out by the same Sensei - martial art teacher. The work showed the contributions that the practice of martial art Karatê provides in the context of the organization carried out by full time school institutions; notably with regard to the search of the development of educational aspects that go beyond the knowledge of regular disciplines, traditionally taught. These aspects are anchored in the development of skills, attitudes and values that - as was understood institutionally - contribute powerfully to a more wide human formation, embed in the development of self-discipline, self-respect; as well as, consequently, a development of the discipline and respect in the treatment with the others. The research was based on the post-structuralist methodology, with theoretical contributions developed by Michel Foucault, based on concepts such as the care of the self, power and discipline. The philosophy of difference, developed by Friedrich Nietzsche, was also considered in the studies. The research used as a method the case study and as research techniques the nonparticipant observation of the Karate classes held in the full-time school, the participant observation in the Karate classes held in the dojo; as well as interviews with karatekas individuals who started in the full-time school the martial art practice and proceed to the dojo space. We also interviewed a visually impaired subject and a woman karateka mother of another female karateka. The interviews conducted with the karatekas individuals that we accompany brought reflexive problems on their existential/martial evolution, in order to prepare material about the issue of the care of the self.